The impact of Internet access on household dietary quality: Evidence from rural China - Yi Cui; Qiran Zhao; Thomas Glauben; Wei Si (Journal of Integrative Agriculture, 2024)
Over the past few decades, the Internet has rapidly diffused across China. The spread of the Internet has had a profound economic and social impact on Chinese rural areas. Existing research shows that Internet access significantly impacts agricultural production and improves smallholder farmers' income. Beyond these, the Internet can affect other dimensions of social welfare. However, research about the impact of Internet access on dietary quality in rural China remains scarce. This study utilizes multi-period panel data from Fixed Observation Point in rural China from 2009 to 2015 to estimate the impact of Internet access on dietary quality and food consumption of rural households and conducts a causal analysis. Regression models with time and household fixed effects allow robust estimation while reducing potential issues of unobserved heterogeneity. The estimates show that Internet access has significantly increased rural household dietary quality (measured by the Chinese Diet Balance Index). Further research finds that Internet access has increased the consumption of animal products, such as aquatic and dairy products. We also examine the underlying mechanisms. Internet access improves dietary quality and food consumption mainly through increasing household income and food expenditure. These results encourage the promotion of Internet access as a valuable tool for nutritional improvements, especially in rural areas.
Keywords: 630; dietary quality; fixed effect model; Internet access; rural China